Life of Jesus research : an annotated bibliography - Evans, Craig A. (New Testament tools and studies,, 1989)
Life of Jesus Research offers students and scholars annotated bibliographies for all of the major areas of critical scholarship in the historical Jesus, providing complete bibliographical information, annotations, and brief introductions to the various subjects. The work is an indispensable tool for research in this important field of study.